Characteristics of sunscreen application on the face of Brazilian skin cancer patients - Nii, Diana [UNESP]; Espósito, Ana Cláudia Cavalcante [UNESP]; Schimitt, Juliano Vilverde [UNESP]; Peres, Gabriel [UNESP]; Miot, Hélio Amante [UNESP] (GN1 Sistemas e Publicacoes, 2020)
Introduction: Photoprotection is indicated to reduce the exposure to cutaneous actinic damage and it is important to prevent skin cancer. The face is the most irradiated area of the body and is also where skin cancers most commonly occur. Objective: To evaluate the amount of sunscreen applied and its facial coverage in patients previously diagnosed with skin cancer, treated at a Brazilian public institution. Methods: Quasi-experimental study involving 40 patients undergoing skin cancer follow-up. Participants were asked to apply sunscreen on their face, as usual, and the mass used was measured. After, participants were photographed under Wood's light to evaluate the homogeneity of the sunscreens coverage, and facial sunscreen coverage failure. Results: Fourteen (35%) participants applied an estimated amount lower than recommended (2mg/cm2). The regions with smallest coverage were the ears and the H area of the face. Conclusions: The insufficient or heterogeneous sunscreen application on face, neck and ears may promote a false perception of protection, leading to irresponsible exposure. As the population ages and the incidence of skin cancers increases, it is essential to stimulate photoprotection, with appropriate information, especially among high-risk individuals.
Keywords: Skin neoplasms; Sunburn; Sunlight; Sunscreening agents